Production Room Temperature and Humidity Sensor Monitoring System Using Node-Red and Grafana (Sistem Monitoring Sensor Suhu dan Kelembaban Ruangan Produksi Menggunakan Node-Red dan Grafana) - Khoirul Anam; Difa Nur Rofi; Ruci Meiyanti (Progresif: Jurnal Ilmiah Komputer, 2024)
The clients of the TRIAS smart industry project are facing issues with a decline in the quality of their production output. They require a monitoring system capable of tracking temperature and humidity levels in the production area and providing real-time alarm notifications for both parameters. This poses a challenge for the contractors to develop a monitoring system for temperature and humidity changes using temperature and humidity sensors as the data source. The system should display the data and issue alerts while also reducing material costs. The research methodology used in this study includes qualitative methods, literature review, and the SDLC-Waterfall method. The research outcome is the development of a data visualization application for the sensors, which utilizes Grafana as the visualization tool. The temperature and humidity data collected by the sensors are recorded using Node-Red and synchronized to the server. This data is stored in a MySQL database within the server. The data from the database is then synchronized with Grafana to be processed and visualized in the form of easily understandable graphs, with the aim of reducing material costs.Keywords: Grafana; IoT; Monitoring; Node-Red; Temperature and Humidity AbstrakKlien dari project TRIAS smart industry memiliki permasalahan pada hasil produksi yang mengalami penurunan kualitas, mereka membutuhkan sistem monitoring yang bisa memantau Suhu dan Kelembaban pada ruangan produksi, dan memberikan alarm notifikasi suhu dan kelembaban pada ruangan produksi secara realtime. Hal ini menjadi tantangan bagi kontraktor untuk membuat sistem monitoring perubahan suhu dan kelembaban menggunakan alat sensor suhu dan kelembaban sebagai data yang akan ditampilkan dan memberikan peringatan dan melakukan pengurangan biaya pada material. Metode yang digunakan pada penelitian ini adalah metode kualitatif, studi literatur, dan metode SDLC-Waterfall. Hasil penelitian ini membuat sistem aplikasi visualisasi data dari sensor, aplikasi visualisasi tersebut menggunakan Grafana. Data didapat dari sensor suhu dan kelembaban dicatat oleh Node-Red dan disinkronisasi pada Server. Data yang berada di dalam Server, disimpan pada database Mysql. Data dari database, disinkronisasi dengan Grafana untuk diproses dan divisualisasikan untuk menampilkan data berbentuk grafik yang mudah dipahami dengan memangkas biaya material.Kata kunci: Grafana; IoT; Monitoring; Node-Red; Suhu dan Kelembaban.